Improving surface quality of polished parts with cleaning agents and lubricating and cooling fluids - Shoful, Kyrylo (National Technical University "Kharkiv Polytechnic Institute", 2025)
The article analyzes the alignment of a planned dissertation study with the new European research paradigm. It explores the possibilities and prospects of applying innovative methods for cleaning coolant-lubricating fluids (CLFs) to improve the quality of ground surfaces. The relevance of the research is emphasized in the context of sustainability, human-centeredness, and practical impact.
Keywords: grinding; coolant-lubricating fluid; CLF cleaning; impregnation; sustainability; human-centeredness; practical orientation